Bank Funding in Central, Eastern and South Eastern Europe Post Lehman : A 'New Normal'? - Impavido, Gregorio (IMF Working Papers; Working Paper ;, 2013)
CESEE banks are reducing foreign funding sources in response to reduced external imbalances, reduced ability to tap international savings, banking group own strategies, initiatives by some regulators, and consistently with uncertainties surrounding the future of the banking union project. In the medium term, the global regulatory agenda and the high foreign presence and stock of FX loans exert opposite forces on rebalancing trends. In the long-term, any funding 'new normal' will be determined by the future design of the EU financial architecture. In the meantime, limiting leverage, the use of FX loans and promoting aggregate saving through macro policies and capital market reforms will increase resilience against shocks going forward.